Historia, pamięć i nacjonalizm po katalońsku - Kubiaczyk, Filip (Studia Europaea Gnesnensia, 2015)
The article analyses relationships between history and memory in the context of Catalonian nationalism. Its essential aim is to demonstrate how one makes (i.e. uses and abuses) memory in Catalonia. The author seeks to show that Catalonian nationalism means manipulation of history, falsification of sources and distorted interpretations rather than a discourse about the actual history of Catalonia.